Comparison of Selective Media for Isolation of Presumptive Group D Streptococci from Human Feces - Sabbaj, Jacobo (1971)
Pfizer Selective Enterococcus (PSE) agar, a medium containing bile, sodium azide, and esculin, was evaluated for its sensitivity and selectivity for detection and enumeration of presumptive group D streptococci in human feces. SF broth and SF broth plus agar (1.5%), representing selective media in common use, were studied simultaneously. Presumptive group D streptococci were recovered on PSE agar from the feces of all 25 subjects. No growth was observed in 8% of specimens in SF broth. No gram-negative organisms were recovered in any medium. PSE agar has the advantages of selecting out Streptococcus bovis, earlier appearance of distinctive reactions, and lack of requirement for special incubation temperature.